Investigation of the characteristics of the band gap on a refractive index of materials - Филипенко, А.И.; Донсков, А.Н. (Radiotekhnika, 2017)
Propagation of electromagnetic waves in a photonic crystal made of GaAs was considered. The propagation of the transverse component of the electromagnetic radiation (TE wave) in the wavelength range from 0.2 to 2 microns was also considered. Dependence of the characteristics of the photonic band gap on the refractive index of the used material was defined.